Use of social network sites among adolescents with autism spectrum disorder: a qualitative study - Alon-Tirosh, Michal; Meir, Naama (Frontiers in Psychology, 2023)
Background: Social network sites (SNS) have become an integral part of the daily lives of billions of users, including adolescents with autism spectrum disorder (ASD). There is a seeming contrast between ASD, characterized by social communication difficulties, and SNS use, requiring social skills. However, few studies examine these adolescents' personal and subjective experiences on and their self-reports regarding the benefits and difficulties of using them. Methods: This study examines the communication strategies of adolescents with ASD in using SNS, through semi-structured in-depth interviews with 10 adolescents diagnosed with ASD. Results: Findings are on three main aspects: reasons for using SNS, actual SNS use, and social characteristics of ASD as expressed through SNS engagement. Conclusions: The main finding is that SNS use among adolescents with ASD exposes their deficiencies in communication despite providing emotional support. This study highlights the importance of guiding SNS use by adolescents with ASD.